Remote detection of radioactive material using high-power pulsed electromagnetic radiation - Dongsung Kim (Nature Portfolio, 2017)
Detection of hazardous radioactive material far from its source is challenging. Here the authors demonstrate a method with higher sensitivity by utilizing high-power pulsed electromagnetic-wave-induced plasma breakdown, which has potential uses in security and defence.